Construction Noise Prediction On The Earth-Moving Activities - Ong, Guan Lin (2020)
Noise is an undesired sound that could be unpleasant and disruptive to hearing. Almost every human activity is associated with noise exposure, especially in the manufacturing, construction, and transportation industries. Noise occurs in a workplace is termed as occupational noise. Over the years, construction noise has brought many health problems to the construction workers. However, during the planning stage of a construction project, noise prediction is not an easy task. Lack of information and a reliable prediction method are the main factors. Therefore, this project aims to determine the accuracy and reliability of a noise prediction method proposed by Haron, Yahya and Jahya (2012), which are the simple prediction charts. The objectives are to investigate the site properties, predict the sound pressure level, and validate the predicted result against the data collected during field measurement. A total of four case studies that include different movement patterns of earth-moving machines have been done in the construction site. By using the simple prediction charts, the average value of noise levels predicted is found to be slightly higher than the measurement as the machines are impossible to operate at full power throughout the entire measurement period. The accuracy and reliability of the simple prediction charts are also subjected to the machine movement patterns. For the earth-moving machines that have biased working duration at one segment of the sub-site, the simple prediction charts will become not suitable to be used. Particularly, at control points with high standard deviations on the prediction results, like in Case Study D, the R 2 is found to be only 0.041. On the other hand, if the earth-moving machines are working over each point of the sub-sites with almost equal probability, the simple prediction charts can approximate the sound pressure level with “Good” reliability, as demonstrated in Case Studies A and B, with R 2 of 0.996 and 0.987, respectively. For accuracy wise, the highest absolute difference is only 1.6 dBA, which indicates a high accuracy. Based on these results, the simple prediction charts are proven to have the ability to yield accurate and reliable results as long as the assumptions of simple prediction charts can be reasonably achieved. With the aid of these design charts, noise levels arouse from the earth-moving machines can be determined easily, at any point of the construction site.